2009
DOI: 10.1242/jeb.020826
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific effects of prenatal testosterone on nestling plasma antioxidant capacity in the zebra finch

Abstract: SUMMARYTrans-generational transfer of non-genetic, maternal resources such as hormones can have a substantial influence on offspring phenotype in many vertebrate species. In birds, maternal androgens enhance both growth and competitive behaviour, but also suppress the immune system. It has been hypothesised that high levels of egg androgens could also influence the prooxidant-antioxidant balance through their positive effect on growth and metabolism. We tested this hypothesis in the zebra finch (Taeniopygia gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 47 publications
0
40
1
Order By: Relevance
“…higher in T-injected birds), although the difference was not significant. By contrast, Tobler and Sandell (Tobler and Sandell, 2009) found lower plasma antioxidant levels in male, but not in female, zebra finches (Taeniopygia guttata) hatched from T-injected yolks. These opposite results might be due to disparities in the methods used to assess antioxidants.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…higher in T-injected birds), although the difference was not significant. By contrast, Tobler and Sandell (Tobler and Sandell, 2009) found lower plasma antioxidant levels in male, but not in female, zebra finches (Taeniopygia guttata) hatched from T-injected yolks. These opposite results might be due to disparities in the methods used to assess antioxidants.…”
Section: Discussionmentioning
confidence: 70%
“…These opposite results might be due to disparities in the methods used to assess antioxidants. Alternatively, sex-related differences in the antioxidant metabolism of both species might arise owing to the different rearing conditions of nestlings, as, while our study was conducted with wild great tits, Tobler and Sandell (Tobler and Sandell, 2009) studied zebra finches in captivity, which could result in the availability of antioxidants being drastically different between the studied populations. Tobler and Sandell (Tobler and Sandell, 2009) suggested that yolk T could have programmed the nestling metabolism, leading to a higher T production in males, and ultimately, to a weaker TAS.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that higher concentrations of yolk testosterone might directly or indirectly (i.e. through an increased growth rate [30]) impair antioxidant defences and increase the production of reactive oxygen and nitrogen species [8,9]. For example, chicks that have hatched from testosterone-injected eggs suffered from reduced plasma antioxidant levels [8] (zebra finch, Taeniopygia guttata) and DNA damage repair efficiency in response to an oxidative challenge [9] (domestic chickens, Gallus gallus).…”
Section: Discussionmentioning
confidence: 99%
“…through an increased growth rate [30]) impair antioxidant defences and increase the production of reactive oxygen and nitrogen species [8,9]. For example, chicks that have hatched from testosterone-injected eggs suffered from reduced plasma antioxidant levels [8] (zebra finch, Taeniopygia guttata) and DNA damage repair efficiency in response to an oxidative challenge [9] (domestic chickens, Gallus gallus). Our result suggests that species with a fast growth stimulated by high levels of yolk testosterone might counterbalance the negative effects of this developmental strategy on oxidative stress levels by allocating high levels of antioxidants, and particularly vitamin E, to their eggs.…”
Section: Discussionmentioning
confidence: 99%
“…2005), increased energy expenditure (Tobler et al. 2007), reduced antioxidant activity (in males only: Tobler and Sandell 2009), nestling survival (Sockman and Schwabl 2000; Muriel et al. 2015), and even maybe long‐term survival (Ruuskanen et al.…”
Section: Introductionmentioning
confidence: 99%